Interval cancers after negative colonoscopy: population-based case-control study - Brenner, Hermann; Chang-Claude, Jenny; Seiler, Christoph; Hoffmeister, Michael (Gut, 2012)
Objective: The risk of colorectal cancer after a previous negative colonoscopy is very low. Nevertheless, interval cancers occur. We aimed to assess the characteristics and predictors of interval cancers after negative colonoscopy. Methods: A population-based case-control study was conducted in Southern Germany in 2003-7. Sociodemographic and tumour characteristics were compared among 78 patients with interval cancers occurring 1-10 years after a negative colonoscopy and 433 colorectal cancers detected at screening. In addition, the indication for the preceding negative colonoscopy and its completeness were compared between patients with interval cancers and 515 controls with a preceding negative colonoscopy. Results: 56.4% of interval cancers occurred among women compared with 33.7% of cases detected by screening (p=0.0001). After adjustment for covariates, female sex (OR 2.28, 95% CI 1.35 to 3.83) and location in the caecum or ascending colon (OR 1.98, 95% CI 1.17 to 3.35) were independently associated with occurrence of interval cancers. The preceding negative colonoscopy was more commonly conducted because of a positive faecal occult blood test (26.0% vs 12.9%, p=0.009) and was more often incomplete (caecum not reached: 18.1% vs 6.7%, p=0.001) among interval cancer cases than among controls. Characteristics of the preceding negative colonoscopy strongly and independently associated with occurrence of interval cancers were follow-up of a positive faecal occult blood test among men (OR 5.49, 95% CI 2.10 to 14.35) and incompleteness among women (OR 4.38, 95% CI 1.69 to 11.30). Conclusions: The observed patterns suggest that a substantial proportion of interval cancers are due to neoplasms missed at colonoscopy and are potentially preventable by enhanced performance of colonoscopy.
Published online first: 26 December 2011
Gesehen am 02.07.2018